2017
DOI: 10.1002/pbc.26685
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience on the use of PET/CT in the management of pediatric post‐transplant lymphoproliferative disorder

Abstract: PET/CT may have an important role in the staging and follow-up of pediatric PTLD. In our cohort, PET/CT was helpful in staging and assessing treatment response and in clarifying equivocal findings on other imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Positron emission computed tomography (PET-CT) and computed tomography (CT) are important radiologic imaging tools for the diagnosis of EBV-PTLDs [1,[39][40][41][42]. In studies in patients with signs and symptoms of PTLDs, PET-CT has demonstrated high sensitivity (90%), specificity (89%), and positive (85%) and negative (93%) predictive values and good capacity for discriminating PTLDs from nonmalignant diseases (88%, 89%, 85%, and 93%, respectively) [40,43].…”
Section: Diagnosis Of Ebv-ptldsmentioning
confidence: 99%
“…Positron emission computed tomography (PET-CT) and computed tomography (CT) are important radiologic imaging tools for the diagnosis of EBV-PTLDs [1,[39][40][41][42]. In studies in patients with signs and symptoms of PTLDs, PET-CT has demonstrated high sensitivity (90%), specificity (89%), and positive (85%) and negative (93%) predictive values and good capacity for discriminating PTLDs from nonmalignant diseases (88%, 89%, 85%, and 93%, respectively) [40,43].…”
Section: Diagnosis Of Ebv-ptldsmentioning
confidence: 99%
“…However, considering the essential differences in pathology and presentation of this disease in the two population groups, diagnostic performance analyses should be carried out separately for children. To date, studies on pediatric PTLD patients have been descriptive in nature, comparing 18 F-FDG PET(/CT) to other imaging modalities (such as CT and MRI) on a lesion by lesion basis and evaluating how additional detected lesions on 18 F-FDG PET(/CT) affected staging and treatment (14,15,18,25). Study populations were often small (range: 7 -34 patients) and in 2 out of the 4 previous studies on this topic, stand-alone 18 F-FDG PET was used instead of the hybrid 18 F-FDG PET/CT (14,18).…”
Section: F-fdg Pet/ct For Response Assessmentmentioning
confidence: 99%
“…18 F-fluoro-2-deoxy-D-glucose ( 18 F-FDG) positron emission tomography (PET)/computed tomography (CT) combines metabolic and anatomic information and may be of value in the diagnosis and treatment evaluation of pediatric PTLD. Preliminary literature suggests that 18 F-FDG PET/CT may be helpful in detecting occult lesions and clarifying findings found on other imaging modalities (13)(14)(15)(16)(17)(18)(19). However, as these previous studies suffered from small sample sizes and frequently mixed children and adults populations, the value of 18 F-FDG PET/CT in pediatric PTLD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Dr. Styczynski for his Letter to the Editor, regarding our paper titled, “Preliminary experience on the use of PET–CT in the management of pediatric post‐transplant lymphoproliferative disease (PTLD).” We note his expertise and appreciate his interest in our paper. We have read with interest his comments and the references quoted.…”
mentioning
confidence: 95%